Building Community Trust: The Effect of Accountability, Transparency, and Community Participation in Village Fund Management - Rahmah, Linda; Nor, Wahyudin (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
This study aims to analyze the effect of accountability, transparency, and community participation on villagers’ trust in the management of village funds. Additionally, it seeks to identify the role of village fund management as an intervening variable linking these three factors to community trust. The research employs a quantitative method, with data collected through questionnaires administered across villages in Kapuas Regency, involving 340 respondents drawn from 148 villages. The survey was conducted to evaluate the impact of accountability, transparency, and community participation in village fund management, and to assess their implications for public trust. Data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS). Results indicate that accountability and community participation exert a significant direct influence on public trust, while transparency affects trust indirectly through village fund management. In this study, village fund management serves as a mediating variable connecting village governance practices with the level of community trust. These findings reinforce the necessity of managing village funds in an accountable, transparent, and participatory manner to build and sustain public trust.